Prove that
[tex]cot(x)*(1-cos(2x))=sin(2x)[/tex]
Proof:
⇒ [tex]\frac{cos(x)}{sin(x)} *(1-cos(2x))=sin(2x)[/tex]
⇒ [tex]\frac{cos(x)}{sin(x)}*(1-(cos^2(x)-sin^2(x)))=2*sin(x)*cos(x)[/tex]
⇒ [tex]\frac{cos(x)}{sin(x)}*(1-cos^2(x)+sin^2(x))=2*sin(x)*cos(x)[/tex]
⇒ [tex]cos(x)*(1-cos^2(x)+sin^2(x))=2*sin(x)*cos(x)*sin(x)[/tex]
⇒ [tex]cos(x)*(1-cos^2(x)+sin^2(x))=2*sin^2(x)*cos(x)[/tex]
⇒ [tex]cos(x) - cos^3(x)+cos(x)*sin^2(x)=2*sin^2(x)*cos(x)[/tex]
⇒ [tex]cos(x)*(1-cos^2(x)) + cos(x)*sin^2(x)=2*sin^2(x)*cos(x)[/tex]
⇒ [tex]cos(x)*sin^2(x) + cos(x)*sin^2(x)=2*sin^2(x)*cos(x)[/tex]
⇒ [tex]2*cos(x)*sin^2(x) = 2*sin^2(x)*cos(x)[/tex]
⇒ [tex]2*cos(x)*sin^2(x) = 2*cos(x)*sin^2(x)[/tex]
Q.E.D.